2015
DOI: 10.3892/mco.2015.627
|View full text |Cite
|
Sign up to set email alerts
|

Role of ventriculoperitoneal shunting in patients with neoplasms of the central nervous system: An analysis of 59 cases

Abstract: Abstract. Approximately 1-5% of patients with cerebral metastasis and ~40% of patients with primary brain tumors suffer from hydrocephalus. These patients often exhibit a poor prognosis. The aim of the present study was to reassess the validity of ventriculoperitoneal shunting (VPS) with the assistance of the general surgeon in oncological patients. A total of 59 patients underwent first-time VPS at the Beth Israel Deaconess Medical Center (Boston, USA) between 2004 and 2012; 40 patients had hydrocephalus from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
0
23
0
1
Order By: Relevance
“…VPS involves placement of a catheter in the lateral ventricle, connected into the peritoneal cavity [ 8 ]. VPS allows for rapid normalization of elevated intracranial pressure (ICP) and is thus commonly employed to relieve symptoms of hydrocephalus [ 5 , 8 , 9 ]. Table 1 depicts studies that have previously reported symptoms and outcomes for patients with leptomeningeal disease-associated HC who have undergone shunting.…”
Section: Current Surgical Optionsmentioning
confidence: 99%
See 3 more Smart Citations
“…VPS involves placement of a catheter in the lateral ventricle, connected into the peritoneal cavity [ 8 ]. VPS allows for rapid normalization of elevated intracranial pressure (ICP) and is thus commonly employed to relieve symptoms of hydrocephalus [ 5 , 8 , 9 ]. Table 1 depicts studies that have previously reported symptoms and outcomes for patients with leptomeningeal disease-associated HC who have undergone shunting.…”
Section: Current Surgical Optionsmentioning
confidence: 99%
“…Table 1 depicts studies that have previously reported symptoms and outcomes for patients with leptomeningeal disease-associated HC who have undergone shunting. Overall, these retrospective series have demonstrated significant improvement in hydrocephalus-associated symptoms following VPS placement, with rates of symptom improvement ranging from 75 to > 90% (Table 1 ) [ 4 , 5 , 9 11 ]. Shunting has also led to marked patient improvements in performance status, with post-surgical Karnofsky Performance Status (KPS) increases of 10–20 points [ 4 , 11 ].…”
Section: Current Surgical Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some examples include vasectomy reversal, 17,18,19 the removal of hernia mesh, 20,21 removal or deactivation of deep brain stimulation, 22,23,24,25 and the removal of a ventriculoperitoneal (VP) shunt. 26,27 Some of these, like the VP shunt or (arguably) a deep brain stimulator, are lifesustaining. Does Huddle want to suggest they cannot be removed even if they function imperfectly?…”
Section: B Establishing More Precise Treatment Categoriesmentioning
confidence: 99%